An Inventory Model with Exponential Demand Rate, Finite Production Rate and Shortages (Journal of Scientific Research, 2009)
The paper contains an order-level inventory model having the demand rate to be a function of time. Here shortages are allowed and completely backlogged. An optimal model is developed by considering exponential demand which minimizes the total average cost. Numerical examples are used to illustrate the developed model. Sensitivity analysis of the optimal solution with respect to major parameters is carried out.  Keywords: Inventory; EOQ; Finite production; Shortages; Exponential demand. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.  DOI: 10.3329/jsr.v1i3.2054              J. Sci. Res. 1 (3), 473-483 (2009)